Combined application of nitrogen, phosphorus, iron, and silicon improves growth and fatty acid composition in marine epiphytic diatoms - Miao Yang; Xin-Yue Xu; Han-Wen Hu; Wei-Dong Zhang; Jing-Yi Ma; Heng-Ping Lei; Qing-Zhi Wang; Xi Xie; Zheng Gong (Frontiers in Marine Science, 2023)
Introduction Marine epiphytic diatoms are natural diets for multiple marine invertebrates, including sea cucumbers, sea urchins, etc. They also act as bioindicators in marine waters to assess water quality of coastal ecosystems. Material and methods We isolated three strains of Navicula and two strains of Nitzschia from macroalgal epiphytes. Combined concentrations of four macroelements, five trace metals, and three vitamins in f/2 medium were optimized for these diatoms using single-factor and orthogonal tests. Results and discussion The biomass productivities for 4-L enlarged cultures of the five isolated diatoms in their exclusively optimized f/2 media all increased by nearly 10-fold relative to f/2 medium, and that of Navicula -1 and Nitzschia -2 reached the highest, i.e., 29.52 ± 1.98 and 30.68 ± 2.84 g m -2 d -1 , respectively. Moreover, the relative abundance of C20:5n3 in the exclusively optimized f/2 medium-cultured Navicula -1 notably rose by 24%, and that in Nitzschia -2 held stable at > 25%. Thus, Navicula -1 and Nitzschia -2 were screened out with outstanding growth traits and improved fatty acid compositions at high levels of combined nitrogen, phosphorus, iron, and silicon. The two diatoms have potential for becoming quality diets for marine aquaculture, and ideal candidates for effective nutrient removal.